STEM-03. WAVE1 KNOCKDOWN ENHANCES THE ANTITUMOR EFFICACY IN PRIMARY GLIOBLASTOMA NEUROSPHERES - Namagiri, Sriya (Neuro Oncol, 2020)
INTRODUCTION: Despite multi-model therapies that include maximal surgical resection, radiation, chemotherapy, and tumor treating fields, the median survival of Glioblastoma (GBM) patients is around 15 months. WASP-family verprolin homologous protein 1 (WAVE1) is a downstream effector that receives signals from small GTPases to regulate the actin cytoskeleton. WAVE1’s interaction with arp2/3 modulates critical roles, such as cell motility and morphologic changes. Expression of WAVE1 has been implicated in leukemia, ovarian, and prostate cancer. In this study, we tested the role of WAVE1 in GBM tumor biology. METHODS: Expression of WAVE1 in normal brain and GBM tumor specimens was assessed by immunohistochemistry (IHC). The relevance of targeting WAVE1 for GBM therapy was evaluated in vitro by western blot, proliferation assay, cell cycle analysis, apoptosis assay, migration assay, and neurosphere formation assay using scrambled and target specific WAVE1-siRNA in patient-derived primary GBM neurospheres (GBMNS). RESULTS: IHC data shows that the expression of WAVE1 is higher in GBM tumor samples than in low-grade gliomas and normal brain tissues. WAVE1 expression is upregulated in GBMNS compared to normal human astrocytes. WAVE1 knockdown significantly decreased the proliferation, migration, and self-renewal of GBMNS without affecting its cell cycle progression. Furthermore, WAVE1 depletion did not show any alterations in the apoptotic cell population, indicating that WAVE1 knockdown has a cytostatic effect on GBMNS. CONCLUSION: Expression of WAVE1 positively correlates with GBM, and its knockdown imparts antitumor efficacy through cytostasis.